Beetles Do It Differently: Two Stereodivergent Cyclisation Modes in Iridoid‐Producing Leaf‐Beetle Larvae. Issue 3 (22nd January 2013) - Kunert, Maritta; Rahfeld, Peter; Shaker, Kamel H.; Schneider, Bernd; David, Anja; Dettner, Konrad; Pasteels, Jacques M.; Boland, Wilhelm
Abstract Larvae of the Chrysomelina species Phaedon cochleariae, Hydrothassa marginella, Phratora vulgatissima, Gastrophysa viridula, Gastrophysa atrocyanea, Gastrophysa cyanea and Gastrophysa polygoni produce the iridoid chrysomelidial (1) to defend themselves against predators. Feeding experiments with a deuterated precursor ([2H5]8‐hydroxygeraniol 9) and in vitro isotope exchange experiments with defensive secretion in 2H2O revealed differences in the cyclisation of the ultimate precursor 8‐oxogeranial (8) to 1, between members of the genus Gastrophysa and all other species. In P. cochleariae, H. marginella and P. vulgatissima1 is most likely produced by a Rauhut–Currier‐type cyclisation via a "transoid dienamine", with loss of a single deuterium atom from C(4) of the precursor. In contrast, members of the genus Gastrophysa cyclise 8 via a "cisoid dienamine" intermediate, with exchange of all three deuterium atoms from the methyl group at C(3). To study whether the different cyclisation modes influence the stereochemistry of 1, the absolute configuration of 1 of the larvae was determined by GC‐MS on a chiral column. In accordance with literature (J. Meinwald, T. H. Jones, J. Am. Chem. Soc.1978, 100, 1883 and N. Shimizu, R. Yakumaru, T. Sakata, S. Shimano, Y. Kuwahara, J. Chem. Ecol.2012, 38, 29), we found (5S, 8S)‐chrysomelidial (1) in H. marginella and P. vulgatissima, but P. cochleariae and all investigated members of the genus Gastrophysa synthesise (5R, 8R)‐chrysomelidial (1).